If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 19 = 9x + -6 Reorder the terms: 19 + 4x = 9x + -6 Reorder the terms: 19 + 4x = -6 + 9x Solving 19 + 4x = -6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 19 + 4x + -9x = -6 + 9x + -9x Combine like terms: 4x + -9x = -5x 19 + -5x = -6 + 9x + -9x Combine like terms: 9x + -9x = 0 19 + -5x = -6 + 0 19 + -5x = -6 Add '-19' to each side of the equation. 19 + -19 + -5x = -6 + -19 Combine like terms: 19 + -19 = 0 0 + -5x = -6 + -19 -5x = -6 + -19 Combine like terms: -6 + -19 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 2w+5=-14w+4(4w-10) | | 2w+5=-14+4(4w-10) | | 1-2x+4x=-11 | | -3(4x-1)+4=13 | | 0.13x+0.5(x-5)=0.01(2x-3) | | Z^7=4Z^5 | | 3/4c+6=18 | | x^4+4x^3=5x^2 | | 15=3-6y | | (x+12)(x+6)=0 | | 2x^3+8x-24x=0 | | 4(5)+x=54 | | kx^2-px+q=0 | | 1/3x-7=-2/3x-9 | | 2(x+4)-(5x-7)= | | 9xsquared=3x-25 | | (c-3)(c-3)=49 | | 17+2(6-3)-3*4= | | 3(x-8)=6 | | (12x-14)=(10x-5x) | | 12x/6-15= | | 6(a-3)=6(a+5)-6a | | (17+2w)(13+2w)-(221)=396 | | n=250/100×2 | | (8/2)/2 | | (2/2(/2 | | 0.95n=n+12 | | 26=3x-7 | | 9=6-(1x+2) | | 20u-67=9(2u-7)+2u-4 | | -(v+6)-3v=-4v-2 | | (5y-6)+(7x-7)=180 |